1984
DOI: 10.1111/j.1365-2125.1984.tb05006.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum protein binding of diazepam and its major metabolite in the neonate during the first postnatal week relate to increased free fatty acid levels.

Abstract: The protein binding of diazepam (D) and its major active metabolite N-desmethyl diazepam (DD) was investigated in vitro in the serum of 14 mothers at birth, 21 foetuses at birth, in 100 neonates between 1 and 11 days of age and in 16 control subjects. The free (unbound) fractions of D and DD in the foetus were similar to those in the controls, but lower than those in the mothers. During the first day of life the free fractions of D and DD doubled in the neonates and subsequently declined slowly to reach near c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…For example, Nau et al reported that the elevations in free fatty acids shortly after birth result in increased free fractions of diazepam and its main metabolite 27 . Ehrnebo et al reported that hyperbilirubinemia reduced the binding of a number of acidic drugs 26 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Nau et al reported that the elevations in free fatty acids shortly after birth result in increased free fractions of diazepam and its main metabolite 27 . Ehrnebo et al reported that hyperbilirubinemia reduced the binding of a number of acidic drugs 26 .…”
Section: Discussionmentioning
confidence: 99%
“…These include the drug and its concentration, the presence of binding competitors, the type and quantity of plasma protein, and the proteins' affinity for the drug. Nau et al (7) observed a twofold increase in the free fraction of diazepam in the serum of neonates that accompanied marked increases in free fatty acids and bilirubin, competitors for albumin-binding sites. Albumin levels progressively rose during a 6-d postgestation monitoring period, but remained significantly lower than in adults.…”
mentioning
confidence: 99%
“…Although therapeutic ranges for drug monitoring are frequently reported in terms of total drug concentration in blood or plasma, the unbound drug concentration provides a better index for monitoring highly-bound compounds. This is particularly true for patients for whom there are disease-or age-related alterations in plasma protein content or composition (4-6) Adverse effects of diazepam in newborns, for example, have been attributed to significant elevations in serum concentrations of unbound parent compound and N-desmethyldiazepam, its major active metabolite (7).…”
mentioning
confidence: 99%
“…Therefore, when the spe cific plasma protein binding percentage of a drug is altered by physiological [2] or patho logical [3][4][5] events, both the pharmacoki netic profile and the expected pharmacologi cal response may be affected. A few endoge nous compounds are known to interact with drug protein binding [6][7][8]. The free fraction plasma concentration should be monitored for compounds that are highly bound or have a narrow therapeutic range [9].…”
Section: Introductionmentioning
confidence: 99%